Anticariogenic Activity of Gnidia glauca (Fresen.) Gilg, Pothos scandens L. and Elaegnus kologa Schlecht - Syed Junaid, Dileep N, Rakesh K.N, Pavithra G.M, Vinayaka K.S, Prashith Kekuda T.R (Journal of Applied Pharmaceutical Science, 2013)
The present study was conducted to estimate total phenolic and flavonoid content and to determine anticariogenic efficacy of methanol extract of Gnidia glauca (Fresen.) Gilg (Thymelaeaceae), Pothos scandens L. (Araceae) and Elaegnus kologa Schlecht (Elaeagnaceae) leaves. Total phenolic and flavonoid content of leaf extracts was determined by Folin-Ciocalteau method and Aluminium chloride colorimetric estimation method respectively. Anticariogenic activity of leaf extracts was assessed against 13 clinical isolates of Streptococcus mutans by Agar well diffusion technique. The contents of total phenolics and flavonoids were higher in G. glauca followed by P. scandens and E. kologa. The extract of G. glauca showed greater inhibition of cariogenic isolates than P. scandens and E. kologa as revealed by wider inhibition zones. The study revealed a correlation between the amount of phenolics and flavonoids present in the extracts and the anticariogenic activity of the extracts. The plants used in this study could be used against dental caries.
Keywords: Gnidia glauca, Pothos scandens, Elaegnus kologa, Tot